PENGARUH TEBAL STYROFOAM CORE TERHADAP BERAT JENIS DAN KEKUATAN TEKAN KOMPOSIT SANDWICH MATRIKPOLYESTER DIPERKUAT SERAT SISAL DAN SERAT POHON PISANG - S. Sinarep; Agus Dwi Catur (Dinamika Teknik Mesin, 2012)
Sandwich composite structure consisting of a core is flanked by two skin.  Therefore, the density of the composite sandwich are influenced by core composites material, the more light core the more lightweight composite produced. So also with the composite compressive strength is also very dependent on the core material. In this paper discussed the influence of core thickness on density and compressive strength of composite sandwich. Sisal fiber or  banana tree fibers that have been woven embedded in polyester composites to strengthen the skin. Composite core (Styrofoam) inserted between the two types of laminated composites to reduce weight and increase rigidity. The variation of the thickness of the core is applied in the manufacture of composites. Made of composite density was measured for specific gravity compared to wood or wood products on the market. Compressive strength of composite was characterized to determine the effect of core thickness on the compressive strength of composites.Research results show that the density of composite decreases with increasing thickness of  styrofoam core. Sandwich composite density is much smaller than the specific gravity of wood or wood products on the market.